Pelatihan terapi massage - Wahyudin Wahyudin; Saharullah Saharullah; Yasriuddin Yasriuddin (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The Community Partnership Program (PKM) partner is the Pa'rappunganta Health Massage Clinic, the community at the Pa'rappunganta Youth Organization. The problem is: (1) lack of knowledge about the basics of anatomy and physiology and mechanical movements in doing massage, (2) lack of skills and not systematic in conducting massage or massage manifulasi, (3) Partner's understanding of massage or massage for patient health is still completely lacking. External targets are members of the Pa'rappunganta Health Massage Clinic, the community for the Pa'rappunganta Youth Organization. The method used is: lectures, demonstrations, questions and answers, and assistance. The results achieved are (1) partners have knowledge of the basics of anatomy and physiology and mechanical movements in doing massage, (2) partners have skills in performing massage or massage, (3) partners have an understanding of massage or massage for patient health.